Cultivating Students' Critical Thinking: A Comprehensive Approach with the Integrative Collaborative Problem-solving (ICoPS) Conceptual Model - Sujatmika, Sigit; Masykuri, Mohammad; Prayitno, Baskoro Adi; ‎ , Sutarno (KnE Social Sciences, 2024)
This research aims to develop an innovative learning model to cultivate students’ critical thinking skills. The formulated model is anchored in Problem-Based Learning (PBL) principles, a pedagogical approach highly endorsed by experts for its efficacy in enhancing critical thinking abilities. We endeavor to optimize the application of PBL to enhance the overall joyfulness of the learning experience. This research method uses DBR by Reeves, which includes: (1) identifying and analyzing problems by researchers and practitioners in collaboration, (2) development of solutions informed by existing design principles and technology innovation, (3) iterative cycles of testing and refinement of solutions in practice, and (4) reflection to produce “design principles” and enhance solution implementation in practice. Currently, the research is in stage two. In the first stage of DBR, the data were collected using a questionnaire to determine the obstacles to PBL from the teacher’s perspective and diagnostics of students’ critical thinking using tests. In stage two, we used a literature study to provide theoretical support for learning model developers. The research results are a draft of the Integrative Collaborative Problem Solving (ICoPS) learning model. We developed this model from the PBL and Jigsaw methods involving the TPACK approach. ICoPS syntax is a combination of the three constituent contents. ICoPS syntax includes (1) problem orientation, (2) formation of an expert group, (3) Jigsaw discussion, (4) investigation, (5) presenting of findings, and (6) evaluation. The syntax maximizes students’ critical thinking while maintaining ease and practicality when applied in the classroom. Keywords: problem-based learning, jigsaw discussion, TPACK, critical thinking